STUDIES ON THE CHARACTERIZATION OF POND WATER FOR AQUACULTURE - A.PARITHABHANU, (International Journal of Pharma and Bio Sciences, 2014)
A local perennial pond near Erode city was selected in the present study. The water sample collected from the pond was analyzed and various parameters showed little variations. The pond water was used as a medium to rear the fingerlings of Oreochromis mossambicus to find the suitability of water for aquaculture. As the fingerlings died in the raw pond water, they were reared in various concentrations of pond water to study the growth pattern through length weight relationship. As the pond water exerted very little deviations in growth, it is recommended to monitor, the pond water properly to be utilized for future aquaculture practices.